2016
DOI: 10.1007/s00464-016-5187-0
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic dilation of benign esophageal anastomotic strictures over 16 mm has a longer lasting effect

Abstract: BackgroundThe optimal target of endoscopic dilation of postsurgical esophageal strictures is unknown. Our aim was to compare the dilation-free period of patients who underwent dilation up to 16 mm with patients who were dilated up to 17 or 18 mm.MethodsWe retrospectively analyzed adult patients who received bougie/balloon dilation for a benign anastomotic stricture after esophagectomy. An anastomotic stricture was defined as dysphagia in combination with a luminal diameter of ≤13 mm at endoscopy. We analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 26 publications
4
19
0
3
Order By: Relevance
“…Unlike a study of esophageal stricture by Gundogdu et al, 22 in which all strictures were caused by corrosive injury, the authors found that strictures of less than 5 cm had a higher EBD success rate. 20 A similar conclusion was found in the study by Cakmak et al, where the treatment effectiveness of EBD was higher, and complication rates were lower in esophageal strictures <5 cm compared with longer ones among patients with corrosive injury or EA related anastomotic stricture. 19 Our study supports this observation, the complication rate is significantly higher in corrosive injury patients with stricture length >5 cm in our series.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Unlike a study of esophageal stricture by Gundogdu et al, 22 in which all strictures were caused by corrosive injury, the authors found that strictures of less than 5 cm had a higher EBD success rate. 20 A similar conclusion was found in the study by Cakmak et al, where the treatment effectiveness of EBD was higher, and complication rates were lower in esophageal strictures <5 cm compared with longer ones among patients with corrosive injury or EA related anastomotic stricture. 19 Our study supports this observation, the complication rate is significantly higher in corrosive injury patients with stricture length >5 cm in our series.…”
Section: Discussionsupporting
confidence: 80%
“…19 van Halsema et al observed that endoscopic dilation over 16 mm significant extended the dilation-free period in comparison with dilation up to 16 mm in patients with benign anastomotic strictures after esophagectomy. 20 The EBD sessions in our patients support this observation. Alkaline corrosive esophagitis was the second most common cause of esophageal stricture in our series; most cases (76.9%) had highest grades of corrosive esophagitis on endoscopy.…”
Section: Discussionsupporting
confidence: 77%
“…As opposed to EBD, a temporary stent acts as a dilator that is kept in place for a substantially longer time of several weeks. Notorious etiologies of BES, associated with a high risk of becoming refractory to repeated EBD are caustic, radiation-induced, and esophagogastric anastomotic strictures [ 36 39 ]. A rising incidence of post-endoscopic strictures is expected as a consequence of new endoscopic interventional treatment modalities in daily clinical practice.…”
Section: Utilization and Limitations Of Esophageal Stentsmentioning
confidence: 99%
“…For anastomotic strictures it has been shown that endoscopic dilation of >16 mm results in a prolongation of the dilationfree period compared with 16 mm. 6 It seems likely that this finding also applies to other types of esophageal strictures.…”
Section: Endoscopic Dilationmentioning
confidence: 91%